Relasi Syukur Dalam Meminimalisir Korupsi Di Indonesia Perspektif Al-Qur’an - mistar, jatim; Hajad, Shohebul (STAI Al-Mujtama Pamekasan, 2024)
Corruption crimes in Indonesia from year to year continue to increase and increasingly variant forms of corruption behavior, so that with all considerations the Indonesian government creates auxiliary institutions devoted to dealing with corruption. The auxiliary institution is the Corruption Eradication Commission (KPK), however, until now, corruption behavior has also increased. Therefore, researchers here offer to deal with corruption in Indonesia with the concept of the Qur'an through the theory of gratitude with a thematic method focused on literature review. From the results of this study, it can be said that human awareness of what has been obtained will form a good character and personality and has implications for daily behavior. Gratitude is a form of positive emotion that can develop into a personality trait with good morality and has implications for influencing individuals in responding to something or situation. So that the positive emotions of gratitude can have a positive impact in preventing corrupt attitudes and behaviors. Where individuals who have high gratitude tend to be resistant to actions that violate morals. Keywords: Gratitude, Corruption, Qur'an